Sustainable harvesting of Conomurex luhuanus and Rochia nilotica by Indigenous Australians on the Great Barrier Reef over the past 2000 years. (December 2019) - Ulm, Sean; McNiven, Ian J.; Aird, Samantha J.; Lambrides, Ariana B.J.
Highlights: Reef flat shellfish were harvested in large numbers on the northern Great Barrier Reef. Size-at-age criteria were applied to Conomurex luhuanus and Rochia nilotica. Morphometric data show no resource depression of C. luhuanus or R. nilotica. Key reef flat shellfish were resilient to relatively low intensity foraging. Abstract: Offshore island colonisation and use around the northern Australian coastline in the mid-to-late Holocene is associated with expanding Aboriginal and Torres Strait Islander populations and intensifying land-use activities. However, few explicit tests of the long-term effects of shellfish forager decision-making and associated impacts on intertidal ecosystems in these newly colonised island environments have been undertaken. We report morphometric analyses on two key reef flat Great Barrier Reef shellfish species, strawberry conch Conomurex luhuanus (n = 360) and top shell Rochia nilotica (n = 45), from two late Holocene archaeological shell midden assemblages on Lizard Island, northeast Queensland. Human foraging pressure was assessed through reconstructions of population age structure across time, highlighting the importance of determining size-at-age habitat preferences and species behaviour patterns when assessing long-term anthropogenic impacts on shellfish populations. Results show no evidence for resource depression across the late Holocene which is broadly in keeping with previous findings at other locales on the Great Barrier Reef, but contrary to expectations of resource intensification models. We conclude that the rich and abundant resources of reef flat environments were resilient to relatively low intensity and likely episodic Indigenous foraging. This sustainability contrasts with the scale and impacts of intensive industrialised harvesting in the historic period.